Ethical Leadership, Psychological Safety, Knowledge Sharing, Employee Creativity, and Organizational Innovation Performance: A Structural Equation Modeling Analysis - El Amrani, Youssef; Beaulieu, Nadine (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective: This study aimed to examine the direct and indirect relationships among ethical leadership, psychological safety, knowledge sharing, employee creativity, and organizational innovation performance and to test a structural model explaining how ethical leadership contributes to innovation outcomes through psychological and behavioral mechanisms.Methods and Materials: This quantitative cross-sectional study was conducted among 548 employees working in medium-sized and large organizations across multiple industries in Canada. Data were collected using standardized questionnaires measuring ethical leadership, psychological safety, knowledge sharing, employee creativity, and organizational innovation performance. The reliability and validity of all measurement instruments were confirmed through Cronbach’s alpha, composite reliability, average variance extracted, and confirmatory factor analysis. Structural equation modeling (SEM) using AMOS 29 was employed to evaluate the measurement and structural models. Model fit was assessed using multiple fit indices, including χ²/df, CFI, TLI, IFI, GFI, AGFI, RMSEA, and SRMR. Direct and indirect effects were examined using bootstrap analysis with 5,000 resamples.Findings: The results demonstrated that ethical leadership had significant positive effects on psychological safety (β = 0.62, p < .001), knowledge sharing (β = 0.29, p < .001), and employee creativity (β = 0.17, p < .001). Psychological safety significantly predicted knowledge sharing (β = 0.47, p < .001) and employee creativity (β = 0.31, p < .001). Knowledge sharing positively influenced employee creativity (β = 0.39, p < .001) and organizational innovation performance (β = 0.18, p < .001). Employee creativity exhibited the strongest direct effect on organizational innovation performance (β = 0.68, p < .001). The structural model demonstrated excellent fit (χ²/df = 2.37, CFI = 0.958, TLI = 0.953, RMSEA = 0.050). Bootstrap analyses confirmed significant indirect effects of ethical leadership on innovation performance through psychological safety, knowledge sharing, and employee creativity. The model explained 71% of the variance in organizational innovation performance.Conclusion: The findings indicate that ethical leadership serves as a critical organizational resource that enhances innovation performance by fostering psychologically safe environments, promoting knowledge-sharing behaviors, and stimulating employee creativity. Organizations that cultivate ethical leadership practices and supportive workplace climates are more likely to achieve sustainable innovation outcomes and maintain competitive advantage in dynamic business environments.